2022
DOI: 10.3389/fimmu.2022.1052182
|View full text |Cite
|
Sign up to set email alerts
|

A novel enterocyte-related 4-gene signature for predicting prognosis in colon adenocarcinoma

Abstract: BackgroundColon adenocarcinoma (COAD) is a fatal disease, and its cases are constantly increasing worldwide. Further, the therapeutic and management strategies for patients with COAD are still unsatisfactory due to the lack of accurate patient classification and prognostic models. Therefore, our study aims to identify prognostic markers in patients with COAD and construct a cell subtype-specific prognostic model with high accuracy and robustness.MethodsSingle-cell transcriptomic data of six samples were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, SERCA3 expression is lower in adenocarcinomas 58 . These results suggest a strong correlation between transition from adenomatous polyposis to adenocarcinoma, COAD development, and aberrant SERCA3 expression 59 . Previous studies have shown that these model genes are related to the occurrence and progression of most tumors, which is consistent with our research results.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, SERCA3 expression is lower in adenocarcinomas 58 . These results suggest a strong correlation between transition from adenomatous polyposis to adenocarcinoma, COAD development, and aberrant SERCA3 expression 59 . Previous studies have shown that these model genes are related to the occurrence and progression of most tumors, which is consistent with our research results.…”
Section: Discussionmentioning
confidence: 67%
“…After manual merging and annotation, we ultimately presented 10 unique cell clusters ( Fig. 3 A) [ 23 , 24 ]. Then, we annotated the clusters based on several canonical marker genes for known cell lineages: T cell (CD3D, CD3E), ICC (ANO1), smooth muscle (MYH11), lymphatic endothelial cell (CCL21), glial cell (S100B), PDGFRA + cell (PDGFRA), macrophages (CD14), mast cell (TPSAB1, TPSB2), Vessel endothelial cell (VWF) and unknow ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the latest therapeutic strategies have achieved substantial progress in patients with mCRC, emerging resistance and lack of predictive biomarkers to current targeted therapies remains a major problem in clinical settings. Further understanding of resistance mechanisms and exploration of biomarkers that can predict the treatment sensitivity and efficacy/toxicity are required to test new evidence-based therapeutic strategies, expand treatment options, and realize personalized medicine [ 145 , 146 , 147 , 148 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%